STRATEGI BRANDING IMAGE DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTS NEGERI 4 PEDAN - Alfian Nurul Khoirulloh; Hafidz Hafidz (PAI RAFAH, 2023)
The quality of education is very influential with branding to introduce educational institutions to the public because educational institutions that have quality educational institutions always attract interest in the community to entrust their daughters to study at the institution. their daughters to study at the institution. Image strategy that The Image Strategy applied at MTs Negeri 4 Pedan Klaten in improving the Quality of Education is in the form of Mirror Image, Multipurpose Image, Current Image of Institutional Quality at MTs Negeri 4 Pedan Klaten improving the Quality of Education in the form of Bulit it, Melt it down, Improve the Quality of Education. Education is in the form of Bulit it, Attach and maintain brand equity. brand. This research using a qualitative descriptive approach was adopted in this investigation. The purpose of qualitative research is to study how reality is understood by those who participate in the research. The method was used to describe and analyze the Image Strategy applied at MTs N 4 Pedan in improving institutional quality. 4 Pedan in improving institutional quality, the research was conducted at MTs N 4 Pedan Klaten. School principals, instructors, support personnel, and students all participated as informants in this study. informants in this study. The researcher used a purposive sampling approach to select and identify informants for this study. This research gathered information through in-depth interviews, document analysis, and participant observation. participant observation. Triangulation was used to ensure the data was reliable by comparing results from multiple sources. Information or data collected from written sources was triangulated with.